Mechanisms of using Financial Management in Developing a Company's Cost Reduction Strategy (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article examines the role and importance of financial management in developing a company’s cost reduction strategy. Effective use of financial management tools enables enterprises to optimize production and operational costs, increase profitability, and ensure financial stability. Based on foreign and domestic experiences, advanced cost reduction strategies and financial management mechanisms are analyzed, and practical recommendations are provided.